ESTIMASI NILAI EKONOMI AIR IRIGASI DAN STRATEGI PEMANFAATANNYA DALAM PENENTUAN IURAN IRIGASI - -, SUMARYANTO; M. SINAGA, BONAR (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 2 Juli 2005, 2012)
The study is aimed to valuate irrigation water and to assess its prospect for water pricing strategy, and implication of optimal cropping pattern on farm's income and rice production. Mathematical programming is applied for the valuation. Strategy of water pricing based on the reconciling efficiency and equity concern. Results of the study show that shadow price of irrigation water were equal to zero on December–May and positive on June–November. Within the positive period, the lowest and highest prices were taken place on June and September respectively. Monthly average of the shadow price was Rp. 40 700/(l/sec), which is equivalent with Rp. 15.75/m3. It is feasible to apply the shadow price for determining ceiling rate of irrigation water charges. Potential method of water pricing is combination of per unit area in wet season and per crop pricing in dry season. Implementation of optimal cropping pattern as well as water pricing was potential to improve both farm's income and irrigation efficiency, but disincentive to increase rice production.
Keywords: Programming, Post Optimality Analysis, Water Pricing